(untitled) (KULT_online, 2016)
In his new and timely book Namibia and Germany. Negotiating the Past the sociologist Reinhart Kößler offers a comprehensive and insightful study on transnational memory politics and subaltern commemorative practices related to the Herero-Nama-genocide, focusing on the specific asymmetrical character of the present debate and the challenges of "postcolonial reconciliation" in such a setting. The main aim is to contribute to an understanding of "actor constellations" within the complex field of transnational memory politics. In doing so, the book critically reflects on the postcolonial situation, raising some urgent questions: where is the space of the affected communities in this transnational memory politics? Do the descendants of the genocide victims actually have a voice in these bilateral talks? The book thus successfully brings together several sites and motives of this postcolonial (memory) conflict in an account of the difficulties and continuing injustices in "transnational communication over a dire past" (p. 10).